Opening the Labor Market to Qualified Immigrants in Absence of Linguistic Barriers - Nicolò Gatti; Fabrizio Mazzonna; Raphaël Parchet; Giovanni Pica (Institute of Labor Economics (IZA), 2022)
This paper investigates the impact of opening the labor market to qualified immigrants who hold fully equivalent diplomas with respect to natives and speak the same mother tongue. Leveraging the 2002 opening of the Swiss labor market to qualified workers from the European Union, we show that the policy change led to a large inflow of young immigrants with the same linguistic background as natives. This, in turn, produced heterogeneous effects on natives wages and employment. While incumbent workers experienced a wage gain and a decrease in the likelihood of becoming inactive, the opposite happened for young natives entering the labor market after the policy change. This is likely the result of different patterns of complementarity/substitutability between same-language immigrants and natives with different levels of labor market experience.
Keywords: F22; J08; J31; J61; 330; worker substitutability; wage effects; qualified immigration; experience